Cranial Migration of Subduroperitoneal Shunt Catheter: Report of Two Cases - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2014)
Subduroperitoneal shunting is a commonly used treatment option for subdural fluid collections. Cranial migration of subduroperitoneal shunt is a rare complication. We report two cases with cranial migration of subduroperitoneal shunts. Both of them had a previous cranial surgery and they secondarily developed subdural fluid collections. These collections were treated with subduroperitoneal shunting using a single peritoneal catheter. Inadequate fixing can result in migration of these single catheters. Elevated intra-abdominal pressure, due to any occasion may also help this migration. We recommend using silk or other braided non-absorbable sutures and anchoring wings for fixing single catheters when used in treatment of subdural fluid collections.
Keywords: Subduroperitoneal; shunt; migration; cranial; DRAINAGE